Особливості функціонування медіатексту - Бакланов, О. В. (ХНУРЕ, 2023)
The article is devoted to a comprehensive approach to defining and studying the features of media text. The peculiarities of media text in the context of diversity of scientific approaches are analyzed, the typology of texts in mass media is investigated